SLEEP DURATION AND SLEEP HYGIENE PRACTICES IN ADOLESCENTS: AGE AND GENDER DIFFERENCES - John, Bindu (Journal of Health and Allied Sciences NU, 2014)
Aim: The study aims at assessing the sleep hygiene practices among Indian adolescents and to identify the age and gender influence on sleep duration and sleep hygiene practices.Methods: The data was drawn from a part of pilot study conducted among adolescents from sixth to 12 grade in India as a part of doctoral research. A stratified random sampling method was used. A total of 58 adolescents, 29 males and 29 females participated in the study. Data was collected using two questionnaires, one for the general demographic data with a part on sleep duration and the second for estimating the sleep hygiene practices.Results: The adolescents slept on an average of 7.68±.99 h during school days, and 8.70±1.63 h on weekends. Middle adolescents slept less than early adolescents. Gender showed no significance with sleep duration, since p-values were >.05 level of significance. The mean sleep hygiene index scores were 28.59 ±6.71. Even though the sleep hygiene scores of males were slightly better than females, it was not statistically significant.Conclusion: Adolescents in the study obtained less than recommended hours of sleep for their age on school days. Sleep hygiene practices were moderately poor among adolescents. Emphasizing good sleep hygiene practices, and integrating sleep promotion programs into daily routines should be considered to improve the sleep problems in adolescents.
Keywords: Sleep; Gender; Sleep Hygiene; Adolescents; Sleep duration